Unusual solute segregation phenomenon in coherent twin boundaries - Cong He (Nature Portfolio, 2021)
Segregation of solute atoms at interfaces affects the properties of alloys and needs to be understood to allow their rational design. Here the authors report an unusual solute segregation phenomenon in a group of Mg alloys, driven by chemical bonding, where solute atoms larger than Mg segregate to compression sites of specific fully coherent twin boundary.